STATUS KERENTANAN NYAMUK AEDES AEGYPTI TERHADAP INSEKTISIDA PERMETHRIN DI KECAMATAN JEMBRANA BALI - Latifa, Kurnia Dwi; Damayanti, Putu Asri; Swastika, I Kadek (E-Jurnal Medika Udayana; Vol 11 No 8 (2022): E-Jurnal Medika Udayana, 2022)
Aedes aegypti is a vector for various life-threatening infectious diseases, such as Dengue Hemorrhagic Fever (DHF). Control of Ae. aegypti using permethrin insecticide has been carried out in various areas including Jembrana. However, irrational use of insecticides has the potential to cause resistance, so it is necessary to evaluate the use of permethrin by testing the susceptibility status of Ae. aegypti . This research is a descriptive study using the bioassay test of the Ae aegypti according to WHO standards. The primary data used is the mortality rate of Ae. aegypti that was exposed to the insecticide permethrin with a concentration of 0.25%. The results of this study showed that the percentage of mosquitoes that experienced knockdown after exposure to insecticides for 1 hour was 96.25% and after holding for 24 hours the percentage of mosquito mortality became 100%. The conclusion of this study is the level of susceptibility of Ae. aegypti in Jembrana District is susceptible. Expanding the range of the sampling area and the use of a more diverse sample generation is needed to better represent the susceptibility status of Ae. aegypti . Keywords: aedes aegypti , mosquito susceptibility status, permethrin.